Recovery of lowland dipterocarp forests under the Malayan uniform system - Hamzah, Mohd Zaki; Ibrahim, Faridah Hanum; Alias, Mohamad Azani; Nik Ab. Majid, Nik Muhamad; Yusoff, Mohd Kamil; Fujiwara, Kazue (The Japan Society of Tropical Ecology, 2004)
Recovery assessment of the logged lowland dipterocarp forests based on phytosociological studies conducted in the state of Negeri Sembilan, Malaysia, showed that the recovery rate of the logged areas depends on the state and degree of harvesting carried out on the stands. The stands that were harvested from 1963 to 1973 under the Malayan Uniform System (MUS) have shown a relatively slow recovery rate. The sites have small average coverage by emergent (ST) trees, ranging from 8% to 14%, and only a few dipterocarps occupy this layer. On the other hand, the stands harvested in the 1950s have recovered towards their original state prior to harvest. The stands recorded an average ST-layer coverage of 24%, T1 layer (57%) and T2 layer (45%). The analysis of species composition recovery and species abundance showed similar trends, with F50 stands appearing similar to the primary forest. The study shows that it takes at least approximately 40 years for the logged-over stands under the MUS to recover to their original state.